Evaluasi Kepuasan Pengguna terhadap Infrastruktur Hunian Tetap Pascabencana dengan Pendekatan Prisma Kinerja - Ni Made Ayu Juli Andjani (Jurnal Konstruksi, 2026)
This study evaluates the performance of post-disaster permanent housing (Huntap) infrastructure in the Talise Huntap Area using the Performance Prism approach. The permanent housing was provided by the government for disaster-affected communities with the objective of not only fulfilling housing needs but also supporting social and psychological recovery. The study focuses on residents’ satisfaction levels, their contributions to facility utilization, the implementation process of development, the capabilities of organizers, and the strategies applied in housing provision. Data were collected through in-depth interviews, field observations, and source triangulation involving residents, managers, and related government agencies. The results indicate variations in satisfaction levels across infrastructure aspects. Neighborhood roads received the highest satisfaction level due to regular maintenance and good accessibility, while Green Open Spaces (RTH) provided social and psychological benefits despite uneven maintenance. Meanwhile, the clean water system (SPAM), sanitation system (SPALDT), and waste management services remained at low satisfaction levels due to unstable distribution, high costs, limited facilities, and suboptimal technical management. Comparisons with other locations show that Talise Huntap performs better in terms of Green Open Spaces but lags behind in clean water services, waste management, and sanitation systems, making the adoption of best practices such as TPS 3R and improved SPALDT management highly relevant. These findings confirm that the quality of infrastructure services depends not only on physical conditions but also on maintenance, technical management, and community participation. The contribution of this study lies in providing comprehensive empirical data regarding residents’ perceptions and satisfaction. The results can serve as a basis for governments and managers in designing improvement strategies, enhancing the efficiency of technical services, and formulating more responsive post-disaster housing development policies. Therefore, this research provides important input for post-disaster infrastructure planning based on user satisfaction and the improvement of the quality of life of affected communities.